The Molecular Basis for Recognition of CD1d/α-Galactosylceramide by a Human Non-Vα24 T Cell Receptor - López-Sagaseta, Jacinto (Public Library of Science, 2012)
CD1d-mediated presentation of glycolipid antigens to T cells is capable of initiating powerful immune responses that can have a beneficial impact on many diseases. Molecular analyses have recently detailed the lipid antigen recognition strategies utilized by the invariant Vα24-Jα18 TCR rearrangements of iNKT cells, which comprise a subset of the human CD1d-restricted T cell population. In contrast, little is known about how lipid antigens are recognized by functionally distinct CD1d-restricted T cells bearing different TCRα chain rearrangements. Here we present crystallographic and biophysical analyses of α-galactosylceramide (α-GalCer) recognition by a human CD1d-restricted TCR that utilizes a Vα3.1-Jα18 rearrangement and displays a more restricted specificity for α-linked glycolipids than that of iNKT TCRs. Despite having sequence divergence in the CDR1α and CDR2α loops, this TCR employs a convergent recognition strategy to engage CD1d/αGalCer, with a binding affinity (∼2 µM) almost identical to that of an iNKT TCR used in this study. The CDR3α loop, similar in sequence to iNKT-TCRs, engages CD1d/αGalCer in a similar position as that seen with iNKT-TCRs, however fewer actual contacts are made. Instead, the CDR1α loop contributes important contacts to CD1d/αGalCer, with an emphasis on the 4′OH of the galactose headgroup. This is consistent with the inability of Vα24− T cells to respond to α-glucosylceramide, which differs from αGalCer in the position of the 4′OH. These data illustrate how fine specificity for a lipid containing α-linked galactose is achieved by a TCR structurally distinct from that of iNKT cells.